Calcium-dependent protein kinase/NADPH oxidase activation circuit is required for rapid defense signal propagation - Dubiella, Ullrich (National Academy of Sciences, 2013)
In animals and plants, pathogen recognition triggers the local activation of intracellular signaling that is prerequisite for mounting systemic defenses in the whole organism. We identified that Arabidopsis thaliana isoform CPK5 of the plant calcium-dependent protein kinase family becomes rapidly biochemically activated in response to pathogen-associated molecular pattern (PAMP) stimulation. CPK5 signaling resulted in enhanced salicylic acid–mediated resistance to the bacterial pathogen Pst DC3000, differential plant defense gene expression, and synthesis of reactive oxygen species (ROS). Using selected reaction monitoring MS, we identified the plant NADPH oxidase, respiratory burst oxidase homolog D (RBOHD), as an in vivo phosphorylation target of CPK5. Remarkably, CPK5-dependent in vivo phosphorylation of RBOHD occurs on both PAMP- and ROS stimulation. Furthermore, rapid CPK5-dependent biochemical and transcriptional activation of defense reactions at distal sites is compromised in cpk5 and rbohd mutants. Our data not only identify CPK5 as a key regulator of innate immune responses in plants but also support a model of ROS-mediated cell-to-cell communication, where a self-propagating mutual activation circuit consisting of the protein kinase, CPK5, and the NADPH oxidase RBOHD facilitates rapid signal propagation as a prerequisite for defense response activation at distal sites within the plant.